Simultaneous Detection of Multiplex-Amplified Human Immunodeficiency Virus Type 1 RNA, Hepatitis C Virus RNA, and Hepatitis B Virus DNA Using a Flow Cytometer Microsphere-Based Hybridization Assay - Defoort, J.-P. (American Society for Microbiology, 2000)
The feasibility of performing a multiplex assay for the detection of human immunodeficiency virus type 1 (HIV-1) and hepatitis C virus (HCV) RNAs and hepatitis B virus (HBV) DNA is demonstrated. This assay is based (i) on the coamplification of a 142-bp fragment from the gag region of the HIV-1 genome and a 142-bp HIV-1 quantitation standard fragment, a 244-bp fragment from the 5′ noncoding region of the HCV genome, and a 104-bp fragment from the pre-C and C gene regions of the HBV genome, using three sets of specific primers; (ii) on the capacity of these four biotinylated PCR products to hybridize to their specific oligonucleotide probe-coated microspheres; and (iii) on the ability of the flow cytometer to discriminate between distinct fluorescent-microsphere categories. Absence of cross-hybridization between the unrelated oligonucleotide probes and PCR products generated by the multiplex reverse transcription-PCR (RT-PCR) and the highly sensitive detection method allowed us to assess unambiguously the HIV-1 viral load and the infectious status of 35 serologically well-established clinical samples and 20 seronegative blood donor plasma samples tested. The results indicate that multiplex RT-PCR and flow cytometer microsphere-based hybridization assays, when combined, provide a rapid, sensitive, and specific method for the quantitation and detection of the major viral agents of infectious diseases in a single plasma sample.